EVALUATION OF THE MANAGEMENT OF NIAWANTIAN VILLAGE-OWNED ENTERPRISES (BUMDES) IN BANTIK LAMA VILLAGE, BEO SUB-DISTRICT, TALAUD ISLANDS DISTRICT - Selpiana Bonte; Hendrik Manossoh; Claudia W M Korompis (ACCOUNTABILITY, 2022)
This study aims to evaluate the management of Niawantian Village Owned Enterprises (BUMDes) in Bantik Lama Village, Beo District, Talaud Islands Regency. The method used in this research is descriptive qualitative with interview and documentation data collection methods. The informants in this study were the Head of BUMDes, Secretary of BUMDes, and Treasurer of BUMDes. The results showed that the management of village-owned enterprises in the village of Bantik Lama generally cannot be said to be good because there are still many improvements needed so that financial recording and reporting are not in accordance with Government Regulation No. 11 of 2021. Joint commitment from the village apparatus and also each part in carrying out every responsibility is a success factor for BUMDes Financial Management. Based on the results of the interview, the BUMDes of Niawantian Bantik Lama is currently only being formed so that it has not run optimally. Because it is still in the process of improving and preparing for administrative completeness for Pertamina Desa and Wifi Desa businesses. Theoretically, this research can provide broad implications regarding stewardship theory. Practically, this research has implications for the management of BUMDes Niawantian to be better in managing and reporting BUMDes finances.